Aplicación del beneficio de contratación de personas con discapacidad y su incidencia en la declaración del impuesto a la renta - Sarango Ortega, Michael Bolivar (2015)
The proposal to implement a simulation model for the proper application of the benefit of hiring people with disabilities. Determined as main objective to promote the integration of persons with disabilities generating a profit for the entities in reducing the tax burden. As research in the proper application of benefit what to the development of qualitative research method was used in their techniques of observation and interview for the proper collection of reliable information it was determined. The phases of implementation of the comprehensive proposal have their detailed activities in the given time, the human and financial resources to use in order to reach an understanding of basis provides the application of concluding benefit of promoting the inclusion of people with disabilities and the State Tax Administration and its legal benefits for companies that hire people with disabilities. Therefore it is recommended to devise a strategy for the employment of these people and make a constant update of the of the resolutions of the tax system and the tax authorities promote specific programs and structured on the benefits provided, to ensure that the company have a broader mind and help the economic, social, cultural and professional growth.